Human Factors in Process Plant Operation. - Strobhar, David A. (Momentum Press, 2014)
Call it the Human element in how a refining and chemical process operationis run ... the other side of the machine and control system operationequation. Its value is in lives protected and money saved. This plain English guide to the principles of human factors will enableoperations and control personnel-both the experienced and uninitiated-to understand how to successfully incorporate the concepts withintheir own plants. Through real-world examples, the author explains howhuman factors engineering concepts do, and must, dovetail with processplant design and operation. Offering practical insights,